Is Dealing with Climate Change a Corporation’s Responsibility? A Social Contract Perspective - Unsworth, Kerrie L.; Russell, Sally V.; Davis, Matthew C. (Frontiers in Psychology, 2016)
In this paper we argue that individuals - as members of society – play an important role in the expectations of whether or not companies are responsible for addressing environmental issues, and whether or not governments should regulate them. From this perspective of CSR as a social contract we report the results of a survey of 1066 individuals. The aim of the survey was to assess participants’ belief in anthropogenic climate change, free-market ideology, and beliefs around who is responsible for dealing with climate change. Results showed that both climate change views and free market ideology have a strong effect on beliefs that companies are responsible for dealing with climate change and on support for regulatory policy to that end. Furthermore we found that free market ideology is a barrier in the support of corporate regulatory policy. The implications of these findings for research, policy, and practice are discussed.